TANTANGAN DAN STRATEGI PENGELOLAAN SDM DALAM USAHA MIKRO WARUNG BU SITI - Keisya Putri Balqis; Indah Tri Sari Harahap; Zainarti Zainarti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Micro-enterprises such as Warung Bu Siti play a vital role in supporting the local economy. However, human resource management (HRM) at the micro-business level often faces several challenges, including limited workforce skills, lack of training, and suboptimal recruitment and retention systems. This study aims to identify the main HRM challenges in Warung Bu Siti and to formulate effective HR management strategies. Using a qualitative approach through observation and in-depth interviews, the study reveals that the main challenges include a lack of HR planning, unbalanced workloads, and low employee motivation. Suggested strategies include informal training, performance-based incentive systems, and improved communication between the owner and workers. The findings are expected to serve as a reference for enhancing HRM efficiency and productivity in similar micro-enterprises.